Crosstalk between microbial biofilms in the gastrointestinal tract and chronic mucosa diseases - Wang, Yumeng; Xu, Shixi; He, Qiurong; Sun, Kun; Wang, Xiaowan; Zhang, Xiaorui; Li, Yuqing; Zeng, Jumei (Frontiers in Microbiology, 2023)
The gastrointestinal (GI) tract is the maximal repository of microbiota inside the human body, but the microbial distribution and living modes remain difficult to explain with a proper model. Biofilm, as the predominant form in the microbial ecosystem, serves ideally to link intestinal flora, molecules, and host mucosa cells. It equips bacteria with the ability to colonize ecological positions, interact with host cells, and resist environmental stressors. This work aims to review the relationship between biofilms in the GI tract and chronic mucosa disease including chronic gastritis, inflammatory bowel disease, and colorectal cancer. In each disease, we summarize the representative biofilm makers and their functions such as Helicobacter pylori, adherent-invasive Escherichia coli, and Fusobacterium nucleatum. We believe the biofilm is instrumental to induce chronic mucosa diseases and may perform as a new biomarker for early diagnosis and treatment. With a deeper understanding of the abnormal biofilm formation in the GI tract, we propose a plausible formulation to deal with bacterial resistance, tolerance, and re-occurrence.